Safety Issues of Bulk Cargo Maritime Transport: Seafarers Viewpoint on Risk Factors Occurrence - Ludmila FILINA-DAWIDOWICZ; Joanna SEK; Aleksandra KULETA (Communications of International Proceedings, 2021)
During the shipping different risk factors may occur providing to extraordinary situations development and undesirable consequences. The article aims to analyze the opinions of seafarers on navigation safety, especially risk factors influencing bulk shipping. The marketing research tool was used to conduct investigations. The opinions of 295 seafarers were analyzed. It was stated that seafarers are aware of risks that may occur during the shipping. Among the most threating factors groups the human factors, as well as technical and technological factors were mentioned. The factors within particular groups of human, technical technological, natural and climatic, as well as systemic factors were analyzed in detail. The research results may be of interest for shipping lines and forwarders responsible for bulk cargo transport.
Keywords: Maritime transport; risk factors; seafarers; bulk cargo; navigation safety